CHARACTER EDUCATION VALUES IN 'AYAH' NOVEL BY ANDREA HIRATA (NILAI-NILAI PENDIDIKAN KARAKTER PADA NOVEL 'AYAH' KARYA ANDREA HIRATA) - Winda Dewi Pusvita (Leksema: Jurnal Bahasa dan Sastra, 2017)
Novel is a kind of literary works which loads lots of character education values. It is created by extraordinary imaginative elements. This article aims at describing character education values in the novel entitled Ayah written by Andrea Hirata. The analysis applied psychology of literature approach. The result of analysis shows that in total there are fifteen different character education values found out in the novel, namely religiousity, honesty, discipline, hard work, creativity, independence, democracy, curiousity, national spirit, love country, appreciation, friendly/communicative, love peace, social care, responsibility. It is suggested that the result of this research can be an input for considering the importance of character education values as capitals for the students to face the upcoming era, beneficial for the Indonesian language and literature teacher-learning process, and ideas for further research to develop literary education, particularly related to psychological and character education value aspects.